A review on the production of nanofertilizers and its application in agriculture - Birara Melku Ayenew; Neela Satheesh; Zemenu Birhan Zegeye; Desalegn Adisu Kassie (Heliyon)
Due to the rapid rise in the worldwide population, the need for food is expanding constantly. To boost agricultural productivity large amounts of synthetic fertilizers are used. However, the extensive use of these synthetic fertilizers leads to various environmental and health problems. Nanotechnology (NT) offers significant improvement in the fertilizer fabrication with optimal chemical compositions, enhances nutrient usage competence, reduces environmental influence, and increased plant productivity. Nano fertilizers (NF) are nanomaterials (NM) that contrast significantly from their corresponding bulk materials. The concept of NF technology is highly innovative, utilizing physical, chemical, and biological methods for formulation. Additionally, the precise application and targeted delivery of nano-fertilizers ensures a more sustainable and accurate approach to agriculture. The purpose of this review is to provide an overview of the various types of nano fertilizers and their synthesis by different methods. In addition, applications of the NF and advantages are also given over the conventional pesticides. Information is also given on the current applications and challenges of the NF. NF are more effective and efficient than conservative fertilizers. The use of NF is expanding owing to the positive influence on nutritional superiority and stress resistance in plants.